Probiotic supplements and athletic performance: a review of the literature - Francavilla, V. C.; Bongiovanni, T.; Todaro, L.; de Pietro, V.; Francavilla, G. (Medicina dello Sport, 2017)
Probiotic supplementation traditionally focused on gut health. However, recently, the clinical applications of probiotics have broadened to allergic, metabolic, inflammatory, gastrointestinal and respiratory conditions. Gastrointestinal health is important for regulating adaptation to exercise and physical activity. Several researches conducted in athletes or active individuals indicate modest clinical benefits in terms of reduced frequency, severity and/or duration of respiratory and gastrointestinal illness. The likely mechanisms of probiotic`s action include interaction with the gut microbiota, interaction with the mucosal immune system and immune signaling directed to a variety of organs and systems. Although scientific evidence for an ergogenic effect of probiotics is lacking, probiotics may provide athletes with secondary health benefits that could positively affect athletic performance through enhanced recovery from fatigue, improved immune function, and maintenance of healthy gastrointestinal tract function